2019
DOI: 10.3390/polym11111745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bilayer Nanofibrous Scaffolds Containing Curcumin/Lithospermi Radix Extract on Wound Healing in Streptozotocin-Induced Diabetic Rats

Abstract: Impaired growth factor production, angiogenic response, macrophage function, and collagen accumulation have been shown to delay wound healing. Delayed wound healing is a debilitating complication of diabetes that leads to significant morbidity. In this study, curcumin and Lithospermi radix (LR) extract, which are used in traditional Chinese herbal medicine, were added within nanofibrous membranes to improve wound healing in a streptozotocin (STZ)-induced diabetic rat model. Gelatin-based nanofibers, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…These data indicate an improvement in healing compared to untreated wounds. This result is consistent with previous studies where Cur was found to promote wound healing by increasing collagen deposition (27), fibromy in production, and myofibroblast contraction (28) via its anti-inflammatory and antioxidant activity (26). Compared with the dexamethasone treatment group, the Cur /HA treatment group had good morphology of wound granulation tissue, was rich in collagenous cells, and showed complete reepithelialization.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data indicate an improvement in healing compared to untreated wounds. This result is consistent with previous studies where Cur was found to promote wound healing by increasing collagen deposition (27), fibromy in production, and myofibroblast contraction (28) via its anti-inflammatory and antioxidant activity (26). Compared with the dexamethasone treatment group, the Cur /HA treatment group had good morphology of wound granulation tissue, was rich in collagenous cells, and showed complete reepithelialization.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the wound closure rate was significantly higher than that of the control group at 3, 7, and 14 days post surgery. The epidermal re-epithelialization was also accelerated, the inflammatory cells were significantly reduced, and the anti-inflammatory effect was obvious (26). These data indicate an improvement in healing compared to untreated wounds.…”
Section: Discussionmentioning
confidence: 62%
“…So, restoring expression of TGF-β is a promising strategy in wound healing. Loading a combination of curcumin and lithospermi vadix extract on nanofibrous scaffolds improve wound healing in DM rats partially by stimulation of TGF-β signaling pathway ( Yang et al, 2019a ). Increasing evidence demonstrates that expression of TGF-β3 undergoes upregulation in scar-less wound healing ( Chen et al, 2005 ).…”
Section: Curcumin and Transforming Growth Factor-beta In Different DImentioning
confidence: 99%
“…Such results are in support of a previous study, where poly(3-hydroxybutyric acid-co-3-hydroxy valeric acid) (PHBV) nanofibers (10% w/v polymer), loaded with curcumin (0.1%–0.5% w/v) as active compound, demonstrated excellent biocompatibility with L929 fibroblast cells [ 53 ]. Similarly, two other groups tested the effect of polyvinyl alcohol (PVA) [ 54 ] and gelatin/PVA/chitosan [ 55 , 56 ] electrospun nanofibers containing Lithospermum erythrorhizon extract alone or in combination with curcumin, on L929 fibroblasts during an in vitro indirect cytotoxicity assay. Their results showed that the scaffolds acted beneficially on cell viability and in some cases, enhanced cell proliferation was observed.…”
Section: Resultsmentioning
confidence: 99%